2018
DOI: 10.3390/f9090508
|View full text |Cite
|
Sign up to set email alerts
|

Soil Aggregation and Organic Carbon Dynamics in Poplar Plantations

Abstract: Soil resident water-stable macroaggregates (diameter (Ø) > 0.25 mm) play a critical role in organic carbon conservation and fertility. However, limited studies have investigated the direct effects of stand development on soil aggregation and its associated mechanisms. Here, we examined the dynamics of soil organic carbon, water-stable macroaggregates, litterfall production, fine-root (Ø < 1 mm) biomass, and soil microbial biomass carbon with stand development in poplar plantations (Populus deltoides L. ‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 74 publications
1
20
0
Order By: Relevance
“…Soil fauna populations appeared to be lower when the uptake of water and nutrients were greatest during the stem exclusion stage, leaving fewer resources available for soil fauna [28,59]. In our study system, the available nitrogen tended to be higher in the 10-year-old stands than in the other stands (Table 1), and published data have demonstrated that microbial biomass carbon exhibited the same trend [16]. There was also a strong relationship between the total abundance and soil properties [17], but we lacked the litter data required to analyze the correlation between the litter quantity and soil arthropod activities.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Soil fauna populations appeared to be lower when the uptake of water and nutrients were greatest during the stem exclusion stage, leaving fewer resources available for soil fauna [28,59]. In our study system, the available nitrogen tended to be higher in the 10-year-old stands than in the other stands (Table 1), and published data have demonstrated that microbial biomass carbon exhibited the same trend [16]. There was also a strong relationship between the total abundance and soil properties [17], but we lacked the litter data required to analyze the correlation between the litter quantity and soil arthropod activities.…”
Section: Discussionsupporting
confidence: 52%
“…Stand development following afforestation can reduce the soil pH through the accumulation of biomass [14,15]. There are wide variations in condition during different stand development phases, such as canopy closure, humidity, and other abiotic and biotic factors [16][17][18], which directly or indirectly impact soil arthropod activity [19][20][21][22].Soil arthropod communities are highly dynamic in forests [23], and following their establishment, they are modified by stand development. In European subalpine spruce forests, the abundance of Collembola was higher in young fertile stands, while that of Oribatida was more abundant in mature stands with increased litter input [24,25].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Physical protection takes place in the fine pores of soil microaggregates (0.053 mm < diameter (Ø) < 0.25 mm) in which anoxic conditions prevail or which are inaccessible to, or spatially separated from, microbial decomposers [20,21]. Microaggregates are often formed and stabilized within macroaggregates (Ø > 0.25 mm), the formation of which is fostered primarily by roots [21,22]. Microorganisms, particularly root-associated microorganisms, and organic matter also play key roles in fostering aggregate formation [21][22][23].…”
Section: Physical Protection and Mineral Sorptionmentioning
confidence: 99%
“…Microaggregates are often formed and stabilized within macroaggregates (Ø > 0.25 mm), the formation of which is fostered primarily by roots [21,22]. Microorganisms, particularly root-associated microorganisms, and organic matter also play key roles in fostering aggregate formation [21][22][23]. The sorption of dissolved organic C (DOC) compounds to minerals occurs in large part with the clay fraction [24,25].…”
Section: Physical Protection and Mineral Sorptionmentioning
confidence: 99%